2008
DOI: 10.1016/j.livsci.2007.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and feeding system on feed intake, growth, and meat and carcass characteristics of fattening Assaf lambs

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
29
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 25 publications
21
29
2
1
Order By: Relevance
“…This may be related to the number of replicates per treatment was low. Görgülü et al (1996) and Rodríguez et al (2008) reported that daily weight gain increased by FCF systems, which is similar to the observations in the present study. However, FCF system in the studies of Sahin et al (2003) and Keskin et al (2004) was not associated with increased daily live weight.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This may be related to the number of replicates per treatment was low. Görgülü et al (1996) and Rodríguez et al (2008) reported that daily weight gain increased by FCF systems, which is similar to the observations in the present study. However, FCF system in the studies of Sahin et al (2003) and Keskin et al (2004) was not associated with increased daily live weight.…”
Section: Resultssupporting
confidence: 91%
“…A cafeteria feeding system or offering free-choice of food (free choice feeding, FCF) may be a practical alternative that offers some advantages over conventional compound feeding of fattening lambs (Fedele et al, 2002;Dikmen et al, 2009). Indeed it has been indicated that sheep, reared in a controlled environment can successfully select a diet of adequate intake from a suitable pair of feeds to match their nutritional requirements and have a feed efficiency and body growth rate similar or better than those achieved with conventional feeding system (FS) (Sahin et al, 2003;Askar et al, 2006;Rodríguez et al, 2007Rodríguez et al, , 2008Dikmen et al, 2009). Behavioural responses such as feeding and welfare behaviours are very important in connection with feed intake and feeding management, since it has direct effects on consumption patterns, feedstuff availability and selection of feeds (Keskin et al, 2004;Kaya, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although feeding system in this study appeared to have no effect on thawing loss, cooking loss, pH 24 , a number of studies have reported that these parameters do change along with changes in feeding system (Skapetas et al, 2006;Rodriguez et al, 2008;Santos et al, 2008). However, our findings are in agreement with the findings of Cerdeno et al, (2006) who found no significant differences neither in meat pH value nor in colour between different feeding practices.…”
Section: Resultssupporting
confidence: 86%
“…However, many studies have demonstrated differences in carcass and meat quality between older lambs under intensive feeding and pasture-based systems (Carrasco et al, 2009, Luciano et al, 2009, Barbut, 2014. Animals fattened under these two different systems had significantly different carcass fat and meat colour (Barwick, 1980, Priolo et al, 2002, Rodriguez et al, 2008, fatness status (Santos et al, 2002;Santos et al,2008) and meat flavor (Saňudo et al, 2000). Our results related to meat colour disagree with the results of (Peña et al (2005) As shown in Table 5, texture parameters were lower in intensively fed lamb compared to the traditional fed lambs.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional fattening systems for lambs in Mediterranean countries are based on an ad libitum supply of concentrates generally supplemented with cereal straw in separate feeding troughs (Joy et al, 2008;Rodríguez et al, 2008). However, concentrate pellets are being used more often nowadays in order to make feedlot feeding management easier.…”
Section: Introductionmentioning
confidence: 99%